Self review portfolio for the MQA institutional audit - Sharifah Hapsah Syed Hasan Shahabudin, Tan Sri Dato'; Universiti Kebangsaan Malaysia (Bangi, Selangor : Universiti Kebangsaan Malaysia, 2009)
Provides information on the nine areas of evaluation for quality, which is vision, mission, educational goals and learning, curriculum design and delivery, assessment of students, student selection and support services, academic staff, educational resouces, programme monitoring and review, leadership, governance and administration and continual quality improvement
Submitted by Prof. Tan Sri Dato' Dr. Sharifah Hapsah Syed Hasan Shahabudin
System requirements: Adobe Reader
Keywords: Quality assurance; Quality control